2005
DOI: 10.1186/ar1702
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cartilage destruction in the arthritides is thought to be mediated by two main enzyme families: the matrix metalloproteinases (MMPs) are responsible for cartilage collagen breakdown, and enzymes from the ADAMTS (a disintegrin and metalloproteinase domain with thrombospondin motifs) family mediate cartilage aggrecan loss. Many genes subject to transcriptional control are regulated, at least in part, by modifications to chromatin, including acetylation of histones. The aim of this study was to examine the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(58 citation statements)
references
References 60 publications
2
53
2
Order By: Relevance
“…Therefore, the suppression of type II collagen expression by HDAC inhibitors suggests that HDAC activity is required for the maintenance of cartilage homeostasis. In contrast to our current results, it has been suggested that HDAC is a target for the suppression of cartilage degradation (33,34). This is based on reports that HDAC inhibitors suppress the ability of IL-1␣ and oncostatin M to enhance the expression of the matrix metalloproteinase gene in SW1353 chondrosarcoma cells and primary human chondrocytes (34) and that HDAC inhibitors modulate the expression of genes involved in the pathogenesis of adjuvant-induced rheumatoid arthritis (35).…”
Section: Hdac Regulates the Growth And Differentiation Of Variouscontrasting
confidence: 97%
See 1 more Smart Citation
“…Therefore, the suppression of type II collagen expression by HDAC inhibitors suggests that HDAC activity is required for the maintenance of cartilage homeostasis. In contrast to our current results, it has been suggested that HDAC is a target for the suppression of cartilage degradation (33,34). This is based on reports that HDAC inhibitors suppress the ability of IL-1␣ and oncostatin M to enhance the expression of the matrix metalloproteinase gene in SW1353 chondrosarcoma cells and primary human chondrocytes (34) and that HDAC inhibitors modulate the expression of genes involved in the pathogenesis of adjuvant-induced rheumatoid arthritis (35).…”
Section: Hdac Regulates the Growth And Differentiation Of Variouscontrasting
confidence: 97%
“…In contrast to our current results, it has been suggested that HDAC is a target for the suppression of cartilage degradation (33,34). This is based on reports that HDAC inhibitors suppress the ability of IL-1␣ and oncostatin M to enhance the expression of the matrix metalloproteinase gene in SW1353 chondrosarcoma cells and primary human chondrocytes (34) and that HDAC inhibitors modulate the expression of genes involved in the pathogenesis of adjuvant-induced rheumatoid arthritis (35). Therefore, our finding that HDAC inhibitors block chondrocyte synthesis of type II collagen, a key molecule in cartilage extracellular matrix, raises questions about the use of HDAC inhibitors to suppress cartilage degradation.…”
Section: Hdac Regulates the Growth And Differentiation Of Variouscontrasting
confidence: 97%
“…26,46,47) Trichostatin A, a HDAC inhibitor, suppressed synovial inflammation and subsequent cartilage destruction in a collagen antibody-induced arthritis mouse model. 26) In this regard, we examined whether or not emodin can influence HDAC expression and activity in IL-1b and LPStreated synoviocytes under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although HDACs are critically involved in diverse biological processes, their function in chondrocyte biology and cartilage diseases have only recently been explored. Recent work indicates that inhibition of HDACs reduces the expression of matrix metalloproteinase in chondrocytes and fibroblasts (7) and, therefore, inhibits arthritis progression in animal models (8,9). Additionally, it has been demonstrated that HDAC4, a Class II enzyme, plays a critical role in the onset of chondrocyte hypertrophy during endochondral ossification (10).…”
mentioning
confidence: 99%